Heart failure and cognitive impairment: A narrative review of neuroimaging mechanism from the perspective of brain MRI - Li, Tong; Bao, Xiangyuan; Li, Lin; Qin, Rui; Li, Cuicui; Wang, Ximing (Frontiers in Neuroscience, 2023)
Both heart failure (HF) and cognitive impairment (CI) have a significant negative impact on the health of the elderly individuals. Magnetic resonance imaging (MRI) can non-invasively detect functional and structural variations in the heart and brain, making it easier to explore the connection between the heart and brain. According to neuroimaging studies, HF patients have a higher chance of developing CI because they have a variety of different types of brain injuries. To examine how HF and CI are influenced by one another, English-language literature was searched in the Web of Science, PubMed EMBASE (OVID), PsycInfo, and Scopus databases. The search terms included “high-frequency,” “brain function,” “brain injury,” “cognition,” “cognitive impairment,” and “magnetic resonance imaging.” Normal brain function is typically impaired by HF in the form of decreased cerebral perfusion pressure, inflammation, oxidative stress, and damage to the BBB, resulting in CI and subsequent HF. Early pathophysiological alterations in patients’ brains have been widely detected using a range of novel MRI techniques, opening up new avenues for investigating the connection between HF and CI. This review aims to describe the pathogenesis of HF with CI and the early diagnostic role of MRI in the heart-brain domain.